التحليل البعدي لبرامج التدخل باستخدام الأساليب التنموية الحاسوبية لتحسين التعرف على الانفعالات الوجهية لدى ذوي اضطرابات التوحد - خاطر، شيماء شكري; عامر، فاتن طلعت قنصوه (الجمعية المصرية للمعالجين النفسيين ( جمعن ), 2017)
Objectives: The current study aims at providing systematic meta analysis of the studies, with a focus, on using computer technologies to improve the recognition of facial emotions among people with autism spectrum, this is to; find out the best of these technologies to improve the recognition of facial, emotions, and find out how different the effect size of these programs may be, depending on the age of the sample, sex, and methods of measuring recognition of emotions and thier diagnosis through a return to the (490) study, and after applying the merger and exclusion factors was retained through (18) study. The study results showed that there is some high effect size of intervention programs based on the use computer techniques to improve the recognition of facial emotions; the study also found that there is some high effect size of virtualization techniques compared to the impact of interactive environments programs to improve the recognition of facial emotions, as it turns out that the high effect size of these techniques varies depending on age and sex in the direction of childhood stage and females. Finally, the study results indicated that the effect size of these techniques varies depending on the methods of measuring facial emotions in the direction of Static methods.
هدفت الدراسة الراهنة إلى تقديم تحليل بعدي منظم للدراسات التي قامت باستخدام الأساليب التنموية الحاسوبية لتحسين التعرف على الانفعالات الوجهية لدى ذوي طيف التوحد وذلك للوقوف على أفضل هذه الأساليب في تحسين التعرف على الانفعالات، ومعرفة مدى اختلاف حجم تأثير هذه البرامج باختلاف المرحلة العمرية للعينة، والنوع، وطرق قياس التعرف على الانفعالات وتشخيصها وذلك من خلال الرجوع إلى (490) دراسة، وبعد تطبيق عوامل الدمج والإقصاء تم الإبقاء على (18) دراسة. وتوصلت نتائج الدراسة إلى وجود حجم تأثير مرتفع لبرامج التدخل القائمة على استخدام الأساليب التنموية الحاسوبية في تحسين التعرف على الانفعالات الوجهية، كما توصلت نتائج الدراسة إلى وجود حجم تأثير مرتفع لبرامج التقنيات الافتراضية مقارنة بتأثير برامج البيئات التفاعلية في تحسين التعرف على الانفعالات، كما اتضح أن حجم تأثير هذه التقنيات يختلف باختلاف المرحلة العمرية والنوع وذلك في اتجاه مرحلة الطفولة والإناث. وأخيراً أشارت نتائج الدراسة إلى أن حجم تأثير هذه التقنيات يختلف باختلاف طرق قياس الانفعالات الوجهية في اتجاه الطرق الثابتة.
Keywords: علم النفس الفسيولوجي -- الانفعالات الوجهية -- اضطراب التوحد -- التقنيات الافتراضية